Shame and blame: Secondary stigma among families of convicted sex offenders. (February 2023) - Evans, Douglas; Trahan, Adam; Laird, Kaleigh
The detriment of incarceration experienced by the formerly incarcerated has been increasingly explored in the literature on reentry. A tangential but equally concerning issue that has recently received more research attention is the effect on family members of the incarcerated. The stigma of a criminal conviction is most apparent among families of convicted sex offenders, who experience consequences parallel to those of their convicted relative. Drawing from interviews with 30 individuals with a family member incarcerated for a sex offence in the United States, this study explores manifestations of stigma due to familial association. The findings suggest that families face negative treatment from social networks and criminal justice officials, engage in self-blame and that the media's control over the narrative exacerbates family members' experiences. Given the pervasiveness of criminal justice system contact, the rapid growth of the sex offender registry in the United States, and the millions of family members peripherally affected by one or both, justice system reforms are needed to ensure that family members are shielded from the harms of incarceration and registration.